2019
DOI: 10.18203/2320-1770.ijrcog20194349
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcome of second baby versus first baby in twins delivered vaginally: a comparative study

Abstract: Background: The incidence of twinning has been increasing due to assisted reproductive technology. Despite substantial concerns over the well-being of the second twin with regard to intra partum events, outcome studies on this issue are conflicting. Some have reported no increase in perinatal complications, while others showed significant associations between labor and delivery of the second twin and increased perinatal morbidity and mortality.Methods: All pregnant women of twin pregnancy at more than 28 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…As in several other studies, 3,8,14 the current work found no association between prolonged IDI and birth weight difference ratio ≥ 20%. Yet, the present analysis did identify a trend toward a higher absolute weight difference in the prolonged IDI group.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As in several other studies, 3,8,14 the current work found no association between prolonged IDI and birth weight difference ratio ≥ 20%. Yet, the present analysis did identify a trend toward a higher absolute weight difference in the prolonged IDI group.…”
Section: Discussionsupporting
confidence: 81%
“…Reasons for this include greater access to assisted reproductive technology (ART), increased rate of ovulation induction, and a rise in maternal age 2 . Twin pregnancies make up approximately 1% of all pregnancies 3 . While attempted vaginal delivery rates in twin pregnancies vary by hospital and by local practice, the success rates of completing a vaginal delivery of both twins are approximately 65%–75% 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…7 8 9 11 20 21 While Mekki et al and Algeri et al reported on a correlation between a 25% intertwin birth weight difference and prolonged IDI, 8 11 Stein et al, Srivastava et al, and Armson et al showed a similar association with a birth weight discordancy of 20% or higher. 7 20 21 The present analysis was consistent with these results, by showing that a birth weight ratio higher than 1.2 was associated with an increased IDI, neonatal acidemia, and lower 5-minute Apgar score. The absolute birth weight had no correlation with the IDI or adverse neonatal outcome.…”
Section: Discussionmentioning
confidence: 97%
“…However, these two studies involved a small sample size and set the IDI of interest at >30 minutes. Other reports 9 10 13 16 21 22 did not address these variables at all. Advanced maternal age and nulliparity have previously been marked as predictors of prolonged second stage of labor in singleton deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation